Efficacy of sotrovimab on omicron BA.2, BA.4 and BA.5 subvariants of sars-cov-2 vs. other early therapies: a systematic review and meta-analysis of literature data - Russo, Antonio; Grimaldi, Pierantonio; Pisaturo, Mariantonietta; Onorato, Lorenzo; Coppola, Nicola (Frontiers in Immunology, 2024)
Background. The aim of this meta-analysis was to ascertain whether sotrovimab was effective in reducing COVID-19 related hospitalization and mortality also in Omicron BA.2, BA.4 and BA.5 subvariants compared to other antivirals effective in index period. Methods. A systematic review and meta-analysis of Randomized Controlled Trials (RCTs) and observational studies comparing the efficacy of early treatment with sotrovimab compared to other early treatment effective in index period, antivirals or monoclonal antibodies (mAbs), in patients with COVID-19 during BA.2, BA.4, BA.5 waves, conducted in accordance with PRISMA guidelines. We searched MEDLINE, Google Scholar and the Cochrane Library. Mortality and hospitalization were defined as outcomes. Results. Four studies were included, allowing a meta-analysis of 8,041 patients. Meta-analysis showed no statistical difference between groups in hospitalization and mortality. Precisely, the RR of mortality showed no difference in the sotrovimab group compared to treatment with other drugs (OR 0.38, 95% CI 0.10-1.49, p<0.166). As regards the rate of hospitalization, no significant difference resulted between the patients treated with sotrovimab and those with other drugs (OR 1.66, 95% CI 0.41-6.66, p=0.477). Interpretation. In conclusion, this meta-analysis showed no significant difference between sotrovimab or other antivirals in reducing COVID-19 evolution in patients with a high risk of progression, considering both hospitalization and mortality.